2009
DOI: 10.1007/s11135-009-9301-4
|View full text |Cite
|
Sign up to set email alerts
|

Using integrated quality assessment for hotel service quality

Abstract: Business hotels, Resort hotels, Importance-Satisfaction(I-S) model, Kano’s model, Services quality improvement,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 33 publications
(46 reference statements)
1
44
0
5
Order By: Relevance
“…This instrument was validated by Ladhari (2010) by applying it to the context of Canadian tourists. The service quality literature in the lodging industry asserts that the evaluation of service quality is multidimensional, (Ekinci, 2002) and that the recommended factors could not be generic (Akbaba, 2006) since some of these can be different in different hotel settings (i.e., resort hotels, business hotels, motels) and cultures (Yang et al, 2011). Table 1 provides a summary of some of the major research studies on service quality measurement that focused on the hotel industry.…”
Section: Service Quality In Lodging Industrymentioning
confidence: 99%
“…This instrument was validated by Ladhari (2010) by applying it to the context of Canadian tourists. The service quality literature in the lodging industry asserts that the evaluation of service quality is multidimensional, (Ekinci, 2002) and that the recommended factors could not be generic (Akbaba, 2006) since some of these can be different in different hotel settings (i.e., resort hotels, business hotels, motels) and cultures (Yang et al, 2011). Table 1 provides a summary of some of the major research studies on service quality measurement that focused on the hotel industry.…”
Section: Service Quality In Lodging Industrymentioning
confidence: 99%
“…In the findings, service was perceived as more important across different segments than the room overall, but cleanliness received higher mean scores. In another study (Yang et al, 2011) that explored the effect of hotel attributes and service on guest experience, the authors concluded that customers evaluate product and service quality based on key attributes the customers think are important. Different hotel attributes and services have varying impacts on hotel guests' lodging experiences and satisfaction.…”
Section: Attribute Performance and Ewom Motivationsmentioning
confidence: 99%
“…Delivering service with a high level of perceived quality can enhance customer loyalty, thus improving customer retention (Hu et al 2009). The effect of service quality on customer satisfaction and its influence on gaining competitive advantage is undeniable (Yang et al 2011). Although many studies have been conducted to identify the most important dimensions of service quality, the research on the comprehensive evaluation of service quality has been limited.…”
Section: Introductionmentioning
confidence: 99%